Conformable electrochemical devices for closed-loop wound management - Li, Jie; Li, Zhangping; Xiao, Jian; Nie, Chenyao (Frontiers in Bioengineering and Biotechnology, 2023)
Chronic wounds arising from accidents, surgeries, or diseases impose a significant clinical and economic burden, underscoring the need for effective solutions to prevent severe complications. Recent advancements in materials science and electrochemical technology have facilitated the development of conformable electrochemical platforms for detection and management, incorporating monitoring, diagnosis, and treatment. Nevertheless, current wound detection and therapy systems face challenges related to the stability and specificity of sensor monitoring, as well as the need for on-site and comprehensive evaluation criteria to offer timely treatment guidance and follow-up care. This review provides a comprehensive overview of the closed-loop management system, emphasizing wound biomarker detection, wound assessment, and on-demand treatment, ultimately culminating in an integrated wound management approach by conformable electrochemical devices. Additionally, we explore the challenges, opportunities, and future prospects of soft and stretchable electrochemical biosensors, with the aim of enhancing the efficiency and timeliness of wound management.